Analisis Disiplin Belajar Siswa Selama Pembelajaran Daring Kelas VIII SMP Negeri 10 Pekanbaru Tahun Ajaran 2021/2022 - Nurma Nurma; Suryanti Suryanti (UIR Press, 2022)
This study aims to determine student learning discipline during online learning for class VIII SMP Negeri 10 Pekanbaru, Academic Year 2021/2022. This research was conducted in November 2021. This research is quantitative descriptive. The method used in this research is a survey method. Data was collected using questionnaires, interviews, and documentation. The sample in this study was 118 students, taken at random or random sampling from class VIII students of SMP Negeri 10 Pekanbaru. The questionnaire distributed consisted of 31 statements. Based on the results of the study, it was shown that the sub-indicators of being obedient and obedient to the rules of learning at school obtained an average percentage of 77.56% with a poor category, preparation in learning activities obtained an average percentage of 76.10% with a good category, attention to learning activities obtained an average percentage of 82.85% with a poor category, having a study plan or schedule obtained an average percentage of 72.27% with a good category, and learning in a supportive place and atmosphere obtained an average an average of 77.82% with a poor category. From the results of this study, it can be concluded that students' learning discipline during online learning for class VIII of SMP Negeri 10 Pekanbaru in the 2021/2022 academic year was obtained on average with a percentage of 77.32% in the good category.